Melatonin benefits to the growth of human annulus fibrosus cells through inhibiting miR-106a-5p/ATG7 signaling pathway - Hai B (Dove Medical Press, 2019)
Bao Hai,1 Yunlong Ma,2 Xiaoyu Pan,1 Lei Yong,1 Chen Liang,1 Guanping He,1 Chenlong Yang,1 Bin Zhu,2 Xiaoguang Liu1 1Department of Orthopedics, Peking University Third Hospital, Beijing 100191, People’s Republic of China; 2The Center for Pain Medicine, Peking University Third Hospital, Beijing 100191, People’s Republic of China Background: Disc degeneration (DD) is one of the common diseases worldwide, which deeply influences normal life and leads to excruciating pain. However, an effective treatment for DD is still not identified.Method: The present study systemically examined the effect of melatonin on annulus fibrosus (AF) cells of patients with DD.Results: Melatonin had the effect of promoting proliferation, inducing autophagy, and suppressing apoptosis on AF cells of patients with DD. Moreover, melatonin contributed to the translation and transcription of autophagy-related protein ATG7 and inhibited the function of miR-106a-5p in AF cells. In addition, the results suggested that miR-106a-5p mediated the expression of ATG7 by directly binding to its 3'UTR in AF cells.Conclusion: This research not only gained a deep insight of melatonin mode of action, but also indicated its potential target signaling pathway in AF cells. Keywords: disc degeneration, melatonin, ATG7, miR-106a-5p